Enhancing Football League Tables. Issue 5 (7th October 2016) - Lau, F. Din-Houn; Gandy, Axel
Abstract: League tables are commonly used to represent the current state of a competition, in football and other sports. But they do not tell the full story. F. Din-Houn Lau and Axel Gandy suggest a few improvements